Jogja Smart Service: Utilization Under Presidential Regulation No. 95/2018 in SPBE Principles - Suryo Bintoro, R.M Hafizh Swardana; Umi Khaera Pati (Media of Law and Sharia, 2025)
The research examines the compatibility of the legal framework for the Jogja Smart Service application with Presidential Regulation Number 95 of 2018, as well as the application of SPBE principles within the Jogja Smart Service. The goal of this study is to assess the alignment of the legal basis for the implementation of the Jogja Smart Service application and the integration of SPBE principles. The research employs a normative-empirical method, analyzing the application of relevant laws and regulations in real-world situations. The findings indicate that while there is legal conformity with the legal foundation for implementing the Jogja Smart Service, its practical application in society is less than ideal. Additionally, the implementation of SPBE principles is not optimal, due to various factors, such as limited public awareness of the Jogja Smart Service application, slow response times from officials in addressing public complaints, and a lack of transparency regarding the security system